Ewolucja rachunku kosztów działań w kierunku oparcia na czasie a analiza wartości działań - Karmańska, Anna (The evolution of activity based costing towards time driven activity based costing and activities value analysis, 2006)
The paper describes a new concept of cost analysis which is known as Time Driven Activity Based Costing (TD ABC). The main goals of this article are: to underline differences between traditional concept of ABC and TD ABC, to point out two dimensions of cost analysis which is focused on activities of business entity and to specify critical stages in analysis of cost activities necessary to be taken on before reengineering of activities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 151-163